2011
DOI: 10.1021/ja201731q
|View full text |Cite
|
Sign up to set email alerts
|

Mild Redox Complementation Enables H2 Activation by [FeFe]-Hydrogenase Models

Abstract: Mild oxidants such as [Fe(C5Me5)2]+ accelerate the activation of H2 by [Fe2[(SCH2)2NBn](CO)3(dppv)(PMe3)]+ ([1]+). The reaction is first order in [1]+ and [H2] but is independent of the E1/2 and concentration of the oxidant. The analogous reaction occurs with D2 and proceeds with an inverse isotope effect of 0.75(8). The activation of H2 is further enhanced with the tetracarbonyl [Fe2[(SCH2)2NBn](CO)4(dppn)]+ ([2]+), the first crystallographically characterized Hox model containing an amine cofactor. These stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 29 publications
3
89
0
Order By: Relevance
“…Using D 2 , we obtained exclusively the corresponding deuterated products [ 1 D] + and [DP( o -tolyl) 3 ] + , as established by 2 H NMR spectroscopy. The reaction of [ 1 ] 2+ and H 2 in the presence of P( o -tolyl) 3 proceeds about four times faster than the previously reported reaction of [ 2 ] + with H 2 in the presence of Cp* 2 Fe + and P( o -tolyl) 3 under identical conditions 18 .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Using D 2 , we obtained exclusively the corresponding deuterated products [ 1 D] + and [DP( o -tolyl) 3 ] + , as established by 2 H NMR spectroscopy. The reaction of [ 1 ] 2+ and H 2 in the presence of P( o -tolyl) 3 proceeds about four times faster than the previously reported reaction of [ 2 ] + with H 2 in the presence of Cp* 2 Fe + and P( o -tolyl) 3 under identical conditions 18 .…”
Section: Resultsmentioning
confidence: 60%
“…Recently, we reported that the addition of mild oxidant to solutions of H ox models allows for facile oxidation of H 2 (ref. 18). This finding suggests that functional models of the H ox state require the presence of both an azadithiolate cofactor as well as a suitably tuned redox cofactor.…”
mentioning
confidence: 99%
“…291 In fact, [ 21 ] + effects H 2 heterolysis in the presence of the mild oxidant [FeCp* 2 ] + (Fc* + ) as well as the (optional) weak base P( o -tolyl) 3 . The reaction proceeds over the course of hours under only 2 atm H 2 at 0 °C to quantitatively afford [ 21 ( μ -H)] + and [HP( o -tolyl) 3 ] + ( k obs = 2.2 × 10 −5 s −1 at 0°C).…”
Section: [Fefe]-h2asesmentioning
confidence: 99%
“…While the oxidation state of nickel in the compound NiÀthioP can be formally assigned as Ni I , the nature of the thiosemicarbazone ligand increases the possibility of a direct interaction between the amide hydrogen and the nickel center. 40,41 NiÀthioP is a representative example that could be used to elucidate how a stable photosynthetic system developed using organic dyes. This indicates that direct metalÀH interaction is able to assist the proton reduction process in the compound NiÀthioP.…”
Section: Introductionmentioning
confidence: 99%